Saccharomyces uvarum isolated from patagonian ciders shows excellent fermentative performance for low temperature cidermaking. (December 2019) - González Flores, Melisa; Rodríguez, María Eugenia; Origone, Andrea C.; Oteiza, Juan Martín; Querol, Amparo; Lopes, Christian Ariel
Abstract: Saccharomyces uvarum has been recovered from natural habitats and traditionally fermented beverages (apple chicha) in Patagonia. However, this species has never been obtained from industrially relevant beverages like wine or cider in the same region. In this work, different strains belonging to the cryotolerant species S. uvarum were recovered from spontaneous cider fermentations carried out at low temperature in Red Delicious apple must. The strain S. uvarum NPCC1420 obtained from this cider and selected for its physiological and technological features, evidenced a better adaptation to the cidermaking process than a previously selected strain obtained from a less industrialized product called apple chicha. Some differences, like a higher ethanol and sulphite tolerance, seemed to be associated with differential domestication pressures suffered by each different strain. Moreover, the most important fermentative features of the strain NPCC1420 were a higher competition capacity than the strain NPCC1314 in non-sterile apple must, as well as significantly higher amounts of glycerol, 2-phenylethanol and 2-phenylethyl acetate than the strain isolated from apple chicha. Graphical abstract: Unlabelled Image Highlights: Saccharomyces uvarum species was recovered for the first time from Patagonian ciders. S. uvarum NPCC 1420 showed the best physiological features for cidermaking. Ciders with high glycerol, 2-phenylethanol and its acetate were produced. Domestication signs like high ethanol and sulphite tolerance were observed.